Sharia Marketing Strategy for Taman Ujung Soekasada Tourism Through Social Media in Boosting Regional Economy : (Case Study: Taman Ujung Soekasada, Tumbu, Karangasem District, Karangasem Regency, Bali Province) - Nastiar Nastiar; Zainul Anwar; Nanda Hidayan Sono (International Journal of Economics and Management Research, 2025)
Current technological advancements can be seen as opportunities by entrepreneurs in the business world. Taman Ujung Soekasada was built by the last king of Karangasem (1890-1945), whose original name was I Gusti Bagus Jelantik. Based on observations made at the location, people can easily access various tourist attractions around the world through social media. However, particularly in Bali, the local government and community show a lack of responsiveness to the marketing of Taman Ujung Soekasada. This research aims to explore how sharia marketing strategies through social media can enhance the local economy at Taman Ujung Soekasada. The method used in this research employs a qualitative approach. The results of this study indicate that the sharia marketing strategies implemented at Taman Ujung reflect realistic and humanistic characteristics. The conclusion and suggestion are that although the utilization of social media is recognized as crucial, there is a need for evaluation and strengthening of social media marketing strategies.